Sape’ as a preservation of the values of Civic Culture Indonesia - Christanto Syam; Yudhistira Oscar Olendo; Zakarias Aria Widyatama Putra; Jagad Aditya Dewantara (Universitas of Muhammadiyah Makassar, 2024)
In this sense, communities' actions and conduct play a crucial role in the preservation and transmission of sape. Dayak civilization still aspires to maintain its integrity in the face of global change, which is the problem in this essay. This writing's goal is to explore this possibility through phenomenological studies and data analysis from Van Kaam, using him as a case study. These findings may be seen in the phenomena of glocalization and glocality within sape. As a result, the Dayak community itself plays a role in the conservation efforts mentioned in the civic culture, having the ability to infuse its efforts with innovation, creativity, change, and renewal. Of course, civilization has been working towards this, but in the current digital era, technology allows for its construction and advancement.